2021
DOI: 10.1038/s41598-021-95113-4
|View full text |Cite
|
Sign up to set email alerts
|

GC-TOF/MS-based metabolomics analysis to investigate the changes driven by N-Acetylcysteine in the plant-pathogen Xanthomonas citri subsp. citri

Abstract: N-Acetylcysteine (NAC) is an antioxidant, anti-adhesive, and antimicrobial compound. Even though there is much information regarding the role of NAC as an antioxidant and anti-adhesive agent, little is known about its antimicrobial activity. In order to assess its mode of action in bacterial cells, we investigated the metabolic responses triggered by NAC at neutral pH. As a model organism, we chose the Gram-negative plant pathogen Xanthomonas citri subsp. citri (X. citri), the causal agent of citrus canker dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 57 publications
3
10
0
Order By: Relevance
“…Interestingly, comparing the pathways affected by eugenol from this study to other studies utilizing the small molecule N-Acetylcysteine (NAC) against Xanthomonas citri subsp. citri showed similar results in the affected pathways [ 46 ]. This study and two previous studies utilizing carvacrol and NAC against Xanthomonas species showed that the pathways of glutathione metabolism; cyanoamino acid metabolism; sulfur metabolism; aminoacyl t-RNA metabolism; glyoxylate and decarboxylate metabolism; glycine, serine, and threonine metabolism; and alanine, aspartate, and glutamate metabolism were regulated by carvacrol, eugenol, and NAC [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Interestingly, comparing the pathways affected by eugenol from this study to other studies utilizing the small molecule N-Acetylcysteine (NAC) against Xanthomonas citri subsp. citri showed similar results in the affected pathways [ 46 ]. This study and two previous studies utilizing carvacrol and NAC against Xanthomonas species showed that the pathways of glutathione metabolism; cyanoamino acid metabolism; sulfur metabolism; aminoacyl t-RNA metabolism; glyoxylate and decarboxylate metabolism; glycine, serine, and threonine metabolism; and alanine, aspartate, and glutamate metabolism were regulated by carvacrol, eugenol, and NAC [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 84%
“…citri showed similar results in the affected pathways [ 46 ]. This study and two previous studies utilizing carvacrol and NAC against Xanthomonas species showed that the pathways of glutathione metabolism; cyanoamino acid metabolism; sulfur metabolism; aminoacyl t-RNA metabolism; glyoxylate and decarboxylate metabolism; glycine, serine, and threonine metabolism; and alanine, aspartate, and glutamate metabolism were regulated by carvacrol, eugenol, and NAC [ 45 , 46 ]. It therefore appears that small molecules frequently target these pathways in Xanthomonas species.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations